2022
DOI: 10.1177/09540083221110031
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilicity and flux properties improvement of high performance polysulfone membranes via sulfonation and blending with Poly(lactic acid)

Abstract: To achieve increased flow and reduce fouling, polymeric membranes can be functionalized with hydrophilic groups such as sulfone, amines, and others. This research has aimed at the sulfonation of Polysulfone (PSU) with various agents and at varying substitution degrees to change its hydrophobic character. PSU was also blended with Poly(lactic acid) (PLA), which is a more hydrophilic polymer. The phase inversion method was used to make PSU, PLA, sulfonated PSU, and PSU/PLA blend-based membranes. Sulfonation degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Enhancing the water affinity of PLLA membranes promotes the attachment, development and multiplication of dermal cells on the membranes [ 59 ]. To enhance the hydrophilicity of PLLA-based nanofibrous membranes, the surface of the membrane is typically subjected to chemical grafting or hydrolysis, which introduces new substances or damages the structure of the membrane to a certain extent [ 60 , 61 ]. However, ammonia plasma treatment offers a convenient and inexpensive approach that allows for the prompt introduction of hydrophilic groups without compromising the structure of the material [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing the water affinity of PLLA membranes promotes the attachment, development and multiplication of dermal cells on the membranes [ 59 ]. To enhance the hydrophilicity of PLLA-based nanofibrous membranes, the surface of the membrane is typically subjected to chemical grafting or hydrolysis, which introduces new substances or damages the structure of the membrane to a certain extent [ 60 , 61 ]. However, ammonia plasma treatment offers a convenient and inexpensive approach that allows for the prompt introduction of hydrophilic groups without compromising the structure of the material [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aseri et al 25 fabricated polyvinylidene fluoride/polylactic acid (PVDF/PLA) hollow fiber ultrafiltration membranes and found that the addition of PLA led to increased water flux, antifouling, and reduction in decomposition temperatures in the synthesized membranes which they report minimizes the membrane's environmental impact. Tasci et al 26 blended sulfonated polysulfone (PSU) with PLA to improve the properties of PSU as a membrane material. The resultant PSU/PLA blend‐based membranes showed optimum compositions with high flux quantities.…”
Section: Introductionmentioning
confidence: 99%